Single-Chain Antibody Fragment VEGF Inhibitor RTH258 for Neovascular Age-Related Macular Degeneration: A Randomized Controlled Study - Holz, Frank G; Dugel, Pravin U; Weissgerber, Georges; Hamilton, Robin; Silva, Rufino; Bandello, Francesco; Larsen, Michael; Weichselberger, Andreas; Wenzel, Andreas; Schmidt, Anne; Escher, Dominik; Sararols, Laura; et al. (Ophthalmology (Rochester, Minn.), 2016)
To assess the safety and efficacy of different doses of RTH258 applied as single intravitreal administration compared with ranibizumab 0.5 mg in patients with neovascular age-related macular degeneration (AMD). Six-month, phase 1/2, prospective, multicenter, double-masked, randomized, ascending single-dose, active-controlled, parallel-group study. A total of 194 treatment-naive patients, aged ≥50 years, with primary subfoveal choroidal neovascularization secondary to AMD. Patients received a single intravitreal injection of RTH258 0.5 mg (n = 11), 3.0 mg (n = 31), 4.5 mg (n = 47), or 6.0 mg (n = 44), or ranibizumab 0.5 mg (n = 61). The primary efficacy end point was the change from baseline to month 1 in central subfield thickness (CSFT) measured by spectral-domain optical coherence tomography. The secondary efficacy end point was the duration of treatment effect measured as time from the initial injection to receipt of post-baseline therapy (PBT) guided by protocol-defined criteria. Adverse events (AEs) were recorded throughout the study. RTH258 demonstrated noninferiority compared with ranibizumab in mean change in CSFT from baseline to month 1 for the 4.5- and 6.0-mg dose groups (margin: 40 μm, 1-sided alpha 0.05). The difference in CSFT change at month 1 comparison with ranibizumab was 22.86 μm (90% confidence interval [CI], -9.28 to 54.99) and 19.40 μm (95% CI, -9.00 to 47.80) for RTH258 4.5 and 6 mg, respectively. The median time to PBT after baseline therapy was 60 and 75 days for patients in the RTH258 4.5- and 6.0-mg groups, respectively, compared with 45 days for ranibizumab. Changes in best-corrected visual acuity with RTH258 were comparable to those observed with ranibizumab. The most frequent AEs reported for the RTH258 groups were conjunctival hemorrhage, eye pain, and conjunctival hyperemia; the majority of these events were mild in intensity. This first-in-human study of RTH258 demonstrated noninferiority in the change in CSFT at 1 month for the 4.5- and 6.0-mg doses compared with ranibizumab and an increase of 30 days in the median time to PBT for the 6.0-mg dose. There were no unexpected safety concerns, and the results support the continued development of RTH258 for the treatment of neovascular AMD.